Analysis of Factors Affecting Indonesian Government Debt - Eva Latifah; Harahap, Muhammad Nasim; Hady Sutjipto; Togi Haidat Mangara; Rizal Syaifudin (Indonesia Banking School, 2024)
This study aims to determine the effect of Gross Domestic Product, New Debt Withdrawal, Exchange Rate, Inflation and Foreign Exchage Reserves on Indonesian Government Debt in 1988-2022. The analysis technique used time series data regression analysis with the Error Correction Model (ECM) method processed using Eviews 10. The result of the study partially show that GDP has a negative and significant effect on government debt in the long term and has no significant effect in the short term, New debt withdrawal has a positive and significant effect in the long term and short term, Exchange rate has a positive and significant effect in the long term and short term, inflation has a negative and significant effect in the long term and short term, and Foreign Exchange Reserves have a positive and significant effect in the long term and short term. Simultaneously, the variables GDP, New debt withdrawal, Exchange rate, Inflation and Foreign Exchage Reserves affect Indonesian Government Debt in 1988-2022.